Integer- and Fractional-Order VCO Using Non-Inertial Amplitude Stabilization and Modern Active Elements - Roman Sotner; Jiri Petrzela; Jan Jerabek; Lukas Langhammer; Josef Polak; Winai Jaikla; Sunti Tuntrakool (My University, 2020)
This paper introduces design of the linearly tunable quadrature voltage-controlled oscillator (VCO) using modern off-the-shelf active elements suitable for the design of electronically adjustable applications. The simplified topology was achieved using non-inertial stabilization of amplitude. It allows targeting adjustability of the oscillation frequency only into lossless integrator part of the topology. This arrangement simplifies the design and the tenability also. Derived symbolical expressions indicate that gain adjustment of used amplifiers (that are still in single path) does not influence amplitude and phase shift ratio of generated waveforms, which is a beneficial feature. The performances of the circuit are tested experimentally in band of units of MHz and results confirmed expected behavior. Initial study of the oscillator with fractional-order capacitors is presented and discussed. Results are supported by laboratory measurements.
Keywords: Colpitts oscillator; Oscillation (cell signaling); Varicap; Advanced Control Systems Design